THE USE OF AUDIO-LINGUAL METHOD IN TEACHING LISTENING COMPREHENSION AT THE SECOND YEAR STUDENTS OF SMK YAPIP MAKASSAR SUNGGUMINASA - Nurdevi Bte Abduh (Universitas Muhammadiyah Makassar, 2016)
Listening is one of the four basic skills in learning a foreign language besides listening, reading, and writing. It has been taught since the students entered a junior high school, however, there are some difficulties faced by vocational school students to listen to the recording. After doing observation, some teachers say that they still have difficulties to teach listening to students since students are not able to express what is on their minds because of their lack of actual language. To help the teachers in teaching listening to students, teachers may use an interesting teaching method to present their teaching materials that also help them in creating a fun class. One of the alternative methods is Audio-lingual teaching method. The objectives of the study were to explain the students’ ability to recognize word meaning in the context and to recognize the content of the text. The design of the research used a collaborative classroom action research (CAR). This kind of research was designed by a group which consisted of teacher and researcher from the educational university. The place of this research was in SMK YAPIP MAKASSAR. The samples in this research were the students at the second year of class 2 Akuntansi 1. After conducting the research, the students’ means score showed the improvement in cycle 2. It is concluded that using audio-lingual could help to improve students’ listening comprehension.Keywords: listening comprehension, audio-lingual, recognizing word meaning and the content of the text, classroom action research